The study of nurses' viewpoint on the use of learning organization principles - Masoomeh Karimi Googhary; Zahra Imani Googhary (Islamic Azad University, 2015)
Introduction: Nowadays due to the dramatic speed of improvements in medical sciences, the use of learning organization approach is essential to make hospitals dynamic. Therefore, applying the learning organization is beneficial as it has practicability. From the viewpoint of Senge, an organization would be a learner if the five principles of personal mastery, mental models, common vision, team learning, and systems thinking are taken into account. According to the central role of nurses in making positive changes in professional nursing activities and responding to patients' needs, the aim of this study was to assess the nurses' viewpoint on the use of learning organization principles in Imam Reza hospital in Sirjan city. Methods: In this cross-sectional study, all staff nurses of Imam Reza hospital constituted the sampling. Senge's learning organization questionnaires, after applying the necessary changes and determining its reliability and validity, was used to gather data. All participants were informed of the goals of the study. Finally, 141 questionnaires were analyzed by SPSS software. Results: The average scores of learning organization for all parameters were higher than the average score of each parameter. There was a significant difference between contract-based nurses with permanently employed nurses and tarhy nurses in the light of the total score of questionnaire, team learning, and systems thinking (P < 0.05). There was also a significant difference between women's viewpoint of mental models, shared vision, systems thinking with those of men (P < 0.05). There was no significant relationship between the age and work history of women with average scores (P > 0.05). Conclusion: Based on the results, the rate of applying learning organization principles in this hospital was more than the average. This indicates the importance of positive perspectives, reinforcement of information, team work, creating a shared perspective of the future, and systems viewpoint. Therefore, stabilizing the employment conditions, having hopes for the future of work, and recruiting younger staff are all highly beneficial in the application of learning organization principles.